2016
DOI: 10.5430/ijh.v2n2p89
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with poor adherence amongst patients receiving antiretroviral therapy at the Oshakati intermediate hospital in Namibia

Abstract: Aim: The aim of this study was to explore factors that influence poor adherence to ART among patients at Intermediate Hospital Oshakati in the Oshana region, which is a rural area in Namibia. Methodology: An explorative, qualitative study was conducted using in-depth interviews among twelve patients (n = 12) identified as poor adherents, which was triangulated with data collected from four key informants (health-workers) in the facility. Eligible participants were purposively selected. Data were audio-recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
(19 reference statements)
0
5
1
Order By: Relevance
“…This study is lined with a study conducted, in Debrebirhan, Ethiopia, the very existence of high prevalence of holy water, has been implicated as hindrance (not taking medicines as a spiritual fear to holy water) to HAART, therefore, this can increase the development of drug resistance and finally increase treatment failure [28]. On the contrary another meta-analysis conducted in Ethiopia have indicated an evidence of positive outcomes of faith healing involving holy water and spiritual aspects that mentally benefit people living with HIV/ AIDS and in other part of Africa there are different reports which shows significant association using different herbal/faith healing and adherence to therapy in HIV patients [11,29]. Ambulatory functional status at baseline is associated risk factor to treatment failure and this is in line with study done in Addis Ababa, Ethiopia [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is lined with a study conducted, in Debrebirhan, Ethiopia, the very existence of high prevalence of holy water, has been implicated as hindrance (not taking medicines as a spiritual fear to holy water) to HAART, therefore, this can increase the development of drug resistance and finally increase treatment failure [28]. On the contrary another meta-analysis conducted in Ethiopia have indicated an evidence of positive outcomes of faith healing involving holy water and spiritual aspects that mentally benefit people living with HIV/ AIDS and in other part of Africa there are different reports which shows significant association using different herbal/faith healing and adherence to therapy in HIV patients [11,29]. Ambulatory functional status at baseline is associated risk factor to treatment failure and this is in line with study done in Addis Ababa, Ethiopia [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are different factors that can affect the ability of HAART to suppress viral replication: viral resistance, and inadequate adherence to therapy, the limited access of paediatric regimens, conducting herbal faith healing and require long term therapy with unknown long term side effect, ambulatory/bedridden functional status at initiation and inadequate dosage guideline for specific HAART and age group, the challenges of paediatric ART adherence and the likelihood of HIV drug resistance development raise great public health concern about virologic failure in children [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…This represented 68% non-adherence in 2014, and 71% in 2015 respectively. Moreover, poor adherence is one of the keys obstacles to successful ART (Bauleth et al, 2016).However, there is a paucity of published data on ART non adherence among male patients in Namibia.…”
Section: Introductionmentioning
confidence: 99%
“…To determine adherence, different methods are being used such as self-report, interview, pharmacy record, pill count and viral load monitoring. Several studies has reported factors related to non-adherence of ART treatment such as lack of family support, depression and confusion (Tjituka et al, 2013 ), stigma and discrimination, spiritual beliefs ,forget to take medication (Bauleth, 2016),side effects of medication (Demeke and Chanie , 2014) and workplace factors (Reda&Biadgilign, 2012). Furthermore, socio-economic factors such as alcohol abuse and transport costs, health related factors such as long waiting times and health professionals' negative attitudes were also reported as factors contributing to non-adherence of ART treatment (Bauleth, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation